(untitled) (Indian Journal of Experimental Biology (IJEB), 2022)
Liver represents a key role in the physiology of animals as most of the metabolic mechanisms occur in it. The pesticides entered into the human body through various routes viz., oral, dermal, inhalation, etc. affect the liver and alter the metabolic rate of the individual. Malathion is an organophosphate pesticide, commonly used in all kinds of crops to protect them from different kinds of pests. Here, we studied the toxicological effects of malathion on the liver of albino rats. Different doses of malathion @ 25, 50, 75 and 100 mg/ kg body wt. were orally administered to the rats for 7 and 15 days. The selected biochemical parameters such as protein, sugar, alkaline phosphatase, acid phosphatase, glutamyl oxalotransaminase (GOT), glutamyl pyruvate transaminase (GPT) and glucose-6- phosphatase dehydrogenase (G6PD) values were measured. Results indicates that the value of protein, acid phosphatase and GPT significantly increases as 5.54+0.99 to 7.35+0.48 mg/g, 14.5+2.50 to 27.37+6.43 mol/g/h and 28.52+3.62 to 37.87+3.94 IU/dL, respectively after treatment. But the sugar, alkaline phosphatase and G6PD value significantly decreases after treatment from 126.12+2.64 to 84.5+10.83mg/g, 29.12+2.64 to 15.5+4.24,6.46 +1.56 mol/g/h to 4.62+1.18 IU/gHb, respectively. Value of GOT increased moderately from 38.5+2.44 to44.87+3.31 IU/dL. The above changes revealed the toxic effects of the pesticide malathion.